Propagation mechanisms and parametric influence in multiple interacting hydraulic fractures: A 3‐D G/XFEM hydro‐mechanical modeling - Mukhtar, Faisal M.; Shauer, Nathan; Duarte, C. Armando (International journal for numerical and analytical methods in geomechanics, 2022)
Using a robust three‐dimensional generalized/eXtended finite element method (G/XFEM) algorithm, this paper presents a comprehensive study on multiple hydraulic fracture propagation and their interactions under different treatment conditions. Aimed at capturing the complex multiphysics behavior, the resulting nonplanar fracture footprints under mixed‐mode conditions are simulated using a formulation, which couples the solid/rock domain equations and the fluid flow within the fractures/crevices. Due to the small length scale of the fracture process zone relative to the surrounding formation size, as typically encountered in tight shale reservoirs, linear elastic fracture mechanics based on a regularized Irwin criterion is adopted to describe the fractured solid/rock response while a power law is used for the fluid flow by assuming a Newtonian fluid behavior. Equipped with the capability for mesh adaptivity and automatic time step search algorithms, the G/XFEM utilized to discretize the resulting system of coupled nonlinear equations allows the adoption of independent meshes for the background solid domain and the fracture surfaces without any matching/compatibility requirement between the two. Fracture propagation directions are decided based on the modes I, II, and III stress intensity factors that are extracted using the displacement correlation method. The presented model is first applied to a pair of misaligned fractures and then to an array of en échelon fractures for qualitative verification against a literature prediction by the boundary element method (BEM) and an observed field behavior, respectively. Next, simulation of several sets and configurations of multiple hydraulic fractures, resulting in a total of 23 parametric studies, are carried out to investigate the influences of fracture spacing, injection fluid viscosity, number of fracture clusters, and the type of remote stress conditions.